Cattle-derived microsatellite markers to study the water buffalo genome - Stafuzza, Nedenia B. [UNESP]; Amaral, M. Elisabete J. [UNESP] (My University, 2013)
Microsatellites are well-known DNA markers used in a variety of studies such as genome mapping, genetic diversity analysis, genetic conservation and phylogenetic studies. Although microsatellites are important markers, their development and characterization demands extensive time and high cost. Thus, before new markers are developed for a particular species, it is worthwhile to test the available markers from related species. In the present study, we evaluate cattle-derived microsatellite markers for genetic studies of water buffalo. Eighty-five percents of a total of 120 microsatellite markers were optimized using buffalo DNA (Bubalus bubalis). The results showed in this paper were also deposited in the National Center for Biological Information database (NCBI) (ProbeDB and UniSTS) for use in population genetic studies of buffalo by the scientific community. The use of heterologous primers significantly reduces the cost of developing specific markers for buffalo, providing a useful short cut for the genetic population analysis and gene mapping studies.
Keywords: Bubalus bubalis; Microsatellites; PCR primers; Water buffalo